SPECIAL SOFTWARE FOR DETECTION OF NIDI WITH UNFAVORABLE TB SITUATION AND HIGH RISK FOR CHILDREN TO BEINFECTED WITH TUBERCULOSIS IN THE REGION - M. N. Golovanova; E. V. Belikova; O. G. Chelnokova; I. A. Efremov; Zh. V. Romanova; N. G. Аverianova (Туберкулез и болезни лёгких)
.